Molecular Characteristics of Staphylococcus aureus Causing Bovine Mastitis between 2014 and 2015 - Li, Tianming; Lu, Huiying; Wang, Xing; Gao, Qianqian; Dai, Yingxin; Shang, Jun; Li, Min (Frontiers in Cellular and Infection Microbiology, 2017)
Staphylococcus aureus is highly pathogenic and can cause diseases in both humans and domestic animals. In animal species, including ruminants, S. aureus may cause severe or sub-clinical mastitis. This study aimed to investigate the molecular profile, antimicrobial resistance, and genotype/phenotype correlation of 212 S. aureus isolates recovered from cases of bovine mastitis from 2014 to 2015 in the Shanghai and Zhejiang areas of China. Nineteen sequence types (STs) were determined by multi-locus sequence typing, while the dominant ST was ST97, followed by ST520, ST188, ST398, ST7 and ST9. Within 14 methicillin-resistant S. aureus (MRSA) isolates and 198 methicillin-susceptible S. aureus (MSSA) isolates, ST97 was the predominant MSSA clone and ST9-MRSA-SCCmecXII-spa t899 was the most common MRSA clone. The MRSA strains showed much higher rates of resistance to multiple antibiotics than did MSSA strains. Compared with other MSSA strains, MSSA ST398 was more resistant to clindamycin, erythromycin and ciprofloxacin. No isolates were resistant to vancomycin, teicoplanin or linezolid. The molecular profiles of the virulence genes varied in different strains. ST520 strains carried seg-sei-sem-sen-seo genes, and ST9 and ST97 harbored sdrD-sdrE genes. Virulence phenotype analysis showed diversity in different clones. Biofilm formation ability was significantly enhanced in ST188 and ST7, and red blood cell lysis capacity was relatively strong in all S. aureus strains of animal origin except ST7. Our results indicate that MSSA was the predominant S. aureus strain causing bovine mastitis in eastern regions of China. However, the presence of multidrug resistant and toxigenic MRSA clone ST9 suggests that comprehensive surveillance of S. aureus infection should be implemented in the management of animal husbandry products.